2014
DOI: 10.1111/apa.12789
|View full text |Cite
|
Sign up to set email alerts
|

Using a urine dipstick to identify a positive urine culture in young febrile infants is as effective as in older patients

Abstract: The leucocyte esterase test showed the same accuracy in young febrile infants as previously reported findings for older children. It predicted positive urine cultures and also revealed important gender differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
3
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 28 publications
2
29
3
1
Order By: Relevance
“…Velasco et al. and Glissmeyer et al. studied the validity of dipstick tests of urine from bladder catheterisation and found that the sensitivity and specificity of leukocyte esterase and, or, nitrites were similar to our results.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Velasco et al. and Glissmeyer et al. studied the validity of dipstick tests of urine from bladder catheterisation and found that the sensitivity and specificity of leukocyte esterase and, or, nitrites were similar to our results.…”
Section: Discussionsupporting
confidence: 88%
“…Many studies have evaluated the accuracy of dipstick tests as a screening technique for UTIs and most of these studies included few infants who were less than 90 days old. Multicentre studies included infants who were less than 90 days old with fever without a source . Velasco et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of microscopy would slightly increase the NPV to 99.2 %, but resulting in eight false-positives for every missed AP. More recently, Velasco et al [27] focusing on the leukocyte esterase test only showed that dipstick use has the same accuracy in young febrile infants as in older children.…”
Section: Diagnosismentioning
confidence: 99%
“…Thus, admission and antibiotic treatment may not be necessary for all these patients 30 31. Most of our patients were well when the result of the urine culture arrived and were managed without antibiotics, on the assumption they were not suffering from a true UTI.…”
Section: Discussionmentioning
confidence: 88%